Perinatal outcome in fresh versus frozen embryo transfer in ART cycles - Ali Aflatoonian; Mohammad Ali Karimzadeh Maybodi; Nastaran Aflatoonian; Nasim Tabibnejad; Mohammad Hossein Amir-Arjmand; Mehrdad Soleimani; Behrouz Aflatoonian; Abbas Aflatoonian (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Despite of higher pregnancy rate after frozen embryo transfer (FET) which is accepted by the majority of researches, the safety of this method and its effect on neonatal outcome is still under debate. Objective: The aim of this study was to evaluate pregnancy and neonatal outcome of FET compare to fresh cycles. Materials and Methods: In this study,1134 patients using fresh ET and 285 women underwent FET were investigated regarding live birth as primary outcome and gestational age, birth weight, gender, multiple status, ectopic pregnancy, still birth and pregnancy loss as secondary outcomes. Results: Our results showed that there is no difference between FET and fresh cycles regarding live birth (65.6% vs. 70.4% respectively). Ectopic pregnancy, still birth and abortion were similar in both groups. The mean gestational age was significantly lower among singletons in FET group compared to fresh cycles (p=0.047). Prematurity was significantly elevated among singleton infants in FET group (19.6%) in comparison to neonates born after fresh ET (12.8%) (p=0.037). Conclusion: It seems that there is no major difference regarding perinatal outcome between fresh and frozen embryo transfer. Although, live birth is slightly increased in fresh cycles and prematurity was significantly increased among singleton infants in FET group